Acceptability of heat-treated oyster meat for kilawin - Plaza, Ina Isabel Balingan; Gabriel, Alonzo (2005.)
ABSTRACT This study explored the possibility of adding thermal treatment of oyster meats (OM) for kilawin preparation. Low- and high- temperature based OM processing were established based on the D-value of Salmonella typhimurium E1366 in OM. Results showed that application of heat significantly enhanced the microbial quality and sensory quality and acceptability of OM used in kilawin preparations. The perceived sensory quality characteristics of OM were insignificantly altered by heat treatment. The results of the study may be used for recommending thermal process as a value-added pre-preparation step for kilawin dish.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Oysters; Cookery (Oysters)